2021
DOI: 10.3390/met11071020
|View full text |Cite
|
Sign up to set email alerts
|

The Orowan Stress Measurement of Twinning Dislocations in Magnesium

Abstract: The interaction between a lattice dislocation and non-shearable precipitates has been well explained by the Orowan bypass mechanism. The calculated additional shear stress facilitates the evaluation of precipitation hardening in metallic alloys. The lack of information about how a twinning dislocation behaves in the same scenario hinders our understanding of the strengthening against twin-mediated plasticity in magnesium alloys. In the current study, the bowing and bypassing of a twining dislocation impeded by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The dislocation character, spatial distribution of precipitates, elastic anisotropy, stacking fault energy, coherency, formation of ledges at the precipitate/matrix interface due to dislocation passage, and formation of an antiphase boundary at the interface, all play a role in determining the applicability limit of the Orowan model. Recent research has demonstrated the potential of nanoscale precipitates to serve as long-lasting dislocation sources for improved ductility and high strength [91][92][93]. As opposed to the Koehler-based model depicted in Figure 8c, multilayers with a significant mismatch in the shear moduli of the layers are covered by dislocations.…”
Section: Strength and Hardness Enhancementmentioning
confidence: 98%
“…The dislocation character, spatial distribution of precipitates, elastic anisotropy, stacking fault energy, coherency, formation of ledges at the precipitate/matrix interface due to dislocation passage, and formation of an antiphase boundary at the interface, all play a role in determining the applicability limit of the Orowan model. Recent research has demonstrated the potential of nanoscale precipitates to serve as long-lasting dislocation sources for improved ductility and high strength [91][92][93]. As opposed to the Koehler-based model depicted in Figure 8c, multilayers with a significant mismatch in the shear moduli of the layers are covered by dislocations.…”
Section: Strength and Hardness Enhancementmentioning
confidence: 98%